Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

f(x)=6x^3-4, g(x)=2x+2, find (g-f)(x)

Sagot :

The value of (g-f)(X) is 2x - 6x³ +6.

what is Function?

An expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable (the dependent variable).

Given:

f(x)= 6x³-4, g(x)= 2x+2

Now,

(g-f)(x)= g(x)-f(x)

= 2x+2-( 6x³-4)

=2x+2- 6x³+4

=2x - 6x³ +6

Learn more about function here:

https://brainly.com/question/12431044

#SPJ1